THE ESSENCE OF INNOVATIVE TEACHING TECHNOLOGIES IN MODERN SCIENTIFIC LITERATURE - Bandura, Liliia (Mountain School of Ukrainian Carpaty, 2018)
The author reveals the issue of innovative technology of teaching in scientific literature. The article analyzes innovative pedagogical technologies as newly created or improved pedagogical systems providing a high level of educational process. In the article it is not ed that the state of modern education depends on their efficiency and innovation. In order to develop innovative technologies and implement them in the educational process, it is necessary to analyze their significance well. An experimental research, conducted by us during communication with students of the 3rd year of study, allows us to analyze the level of awareness of the main concepts of their future professional activities. Detailed analysis and comparison of interpretations of various authors of this concept allows you to better understand its essence and submit your own. A detailed analysis and comparison of interpretations of various authors of this concept makes it possible to better understand its essence and to present our own. We consider such information useful in the development of education in general and in the educational process in particular, since for the first time the integral meaning of the concept of «innovative pedagogical technologies» is derived. According to the concept of the «New Ukrainian School», the progressive development of education is possible only with the qualitative training of future specialists, which, with the use of innovative pedagogical technologies, will have a successful result. The purpose of the article is to reveal the essence of the concept of «innovative pedagogical technologies», using information from the latest publications on this topic. The author used such methods of teaching: analysis and synthesis of information from used literary sources, comparison and systematization, experiment and observation.